Linguistic Taboos in Karonese Culture - Barus, J; Sibarani, R; Saragih, A; ., Mulyadi (KnE Social Sciences, 2018)
This paper investigates the linguistic taboos in the Karonese culture viewed from linguistic anthropology point of view. It concerns with the meaning of taboo based on performance, indexicality, and participation [4]. With this approach, linguistic taboos are explored not only from its lexical or words only, they are viewed from the process of communication totally, included lexical or words, the way to speak, the participants of speaking, and the contexts of communication. The theory used is proposed by Freud (1913/2004: 21), that taboo, on the one hand, is sacred, consecrated, and on the other uncanny, dangerous, forbidden, and unclean. Thus ‘taboo’ has about it a sense of something unapproachable and it is principally expressed in prohibitions and restrictions. Ethnographic method proposed by Spradley (1980) is applied in doing the research. The result shows that the linguistics taboos are classified into taboo in kinship, i.e. between bengkila and permain, turangku and turangku, and mami and kela; context-specific taboos, i.e. words derived from non-taboo words: such as organs of body, animals and supernatural entity, and certain words; and words related to social and physical defects: such as illness, death, and killing; and general taboos, i.e. swearing and unmentionable words. The swearing includes scatology or dirt, sexual organs, sexual acts, mothers or family, ancestors, animals, death, illness, and prostitution. Whereas, unmentionable words include dirty words relating to sex organs, sexual activities, bodily effluvia, micturition and defecation, and naming or addressing family and relatives. Keywords: taboo, kinship, swearing, sexual